Volatilomic fingerprinting from edible flowers. Unravelling some impact compounds behind its attractiveness - Izcara, Sergio (2022)
In recent years edible flowers emerged in gourmet cuisine, giving any dish the beauty of attractive colours, freshness, texture, and aromatic notes. Moreover, they also constitute a potential source of phytochemical compounds associated with beneficial effects on human health. In this work, the volatilomic fingerprinting of 4 different species of edible flowers [blue mallow (Malva sylvestris L.), pomegranate flower (Punica granatum L.), hibiscus (Hibiscus rosa-sinensis L.), and nasturtium (Tropaeolum majus L.)] used in gourmet dishes, was estab lished, and comparatively investigated. The volatile metabolites were extracted by solid-phase microextraction in headspace mode and identified by gas chromatography-mass spectrometry to understand the chemistry behind its attractiveness better. A total of 78 volatile metabolites, belonging to diverse chemical groups were identified. Blue mallow is mainly characterised by sesquiterpenoids (61.5% of the total volatile fraction), whereas in flowers from pomegranate, hibiscus, and nasturtium, terpenoids (56.6%), carbonyl compounds (88.0%) and organo sulfur compounds (98.0%) are the dominant chemical groups, respectively. In blue mallow flowers, τ-muurolene and valencene are the dominant volatiles, followed by α-cubebene and δ-cadinene. Pomegranate flowers are rich in furfural and linalool, while the aldehydes 2-hexenal, hexanal and 2-octenal are dominant volatile metabolites in hibiscus. Benzyl isothiocyanate, a potent antimicrobial agent, accounts for 98% of the total volatile fraction of nasturtium flowers. In addition to flavour notes, some of the identified volatile metabolites present bioactive properties, which could be explored for application in the food, pharmaceutical and cosmetic industries. The volatile metabolites profiles combined with unsupervised principal component analysis facilitated the differ entiation of the edible flowers under investigation, revealing the most related volatile metabolites of each sample, which can be used as markers for the authentication of these valuable food samples.